2014
DOI: 10.1016/j.aju.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of sexual dysfunction in Egyptian women with lower urinary tract symptoms

Abstract: IntroductionFemale sexual dysfunction (FSD) has been reported in 46% of women with lower urinary tract symptoms (LUTS). FSD is a common health problem that remains under-investigated, especially in Eastern communities, where discussion of the issue is considered a taboo. In this study we determined the prevalence of various subtypes of FSD in relation to LUTS in women in Ismailia, Egypt.Patients and methodsThis was a case-control study to assess FSD in women with LUTS in comparison to normal women. In all, 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(39 reference statements)
0
9
0
1
Order By: Relevance
“…This finding duplicates those of previous Egyptian studies. [49,52,53] However, contrary to other papers in Egypt. [10,35] Vaginal delivery and episiotomy were highly significant variables with female sexual dysfunction, this in line with other studies results.…”
Section: Discussionmentioning
confidence: 70%
“…This finding duplicates those of previous Egyptian studies. [49,52,53] However, contrary to other papers in Egypt. [10,35] Vaginal delivery and episiotomy were highly significant variables with female sexual dysfunction, this in line with other studies results.…”
Section: Discussionmentioning
confidence: 70%
“…In current studies, the reason for positive correlation between SD and UI was indicated as the effect of UI on life quality, especially it posed a barrier on satisfaction of women, having coital incontinence, with sexual life. The correlation between SD and UI was reported to develop as a result of extremely active bladder, UI, and pelvic prolapse, in addition to hormone deficiencies that affect pelvic organs 41 .…”
Section: Discussionmentioning
confidence: 99%
“…3 The prevalence of FSD and influencing factors is variable among countries and different areas. 3,8 Assessment of female sexual function and FSD includes questionnaires, structured interviews, and comprehensive case history. Questionnaires are currently the first choice to screen individuals into different FSD categories.…”
Section: Introductionmentioning
confidence: 99%
“…11 Although FSD is a common health problem, it is still underinvestigated particularly in Eastern communities, where its open discussion is considered a taboo. 8 Moreover, the Arabic culture is generally conservative toward sex and female sexuality. 11 How much risk of FSD is prevalent in Saudi Arabia and what exactly is its magnitude are common questions.…”
Section: Introductionmentioning
confidence: 99%